Perception and use of flywheel resistance training amongst therapists in sport - de Keijzer, Kevin L.; Raya-González, Javier; López Samanés, Álvaro; Moreno Perez, Victor; Beato, Marco (Frontiers in Sports and Active Living, 2023)
Flywheel (isoinertial) resistance training is a valid strength training method that has been incorporated in sport for decades, yet little is known about how therapists working in sport apply flywheel resistance training. We aimed to describe and understand current application and perception of flywheel resistance training amongst therapists working in sport. Seventy-three therapists (13.1 ± 10.0 years of experience) started part of this survey with 52 completing the entire electronic questionnaire. Nine multiple choice questions on application and perceptions of flywheel training (prerequisites, use of technology, barriers, and upper- and lower-body exercises) preceded two 6-point Likert scale statements on strength and reduction of injury likelihood. Most therapists (47/73) either used or intended to use flywheel training with their athletes and stated familiarisation would be a priority prior to initiating training. Although more than half suggested they were confident flywheel training could enhance strength (27/52) and muscular prehabilitation outcomes (40/52), many remained unsure. Nonetheless, it appears that therapists would mostly include flywheel training within prehabilitation (40/52) or during the later stages of rehabilitation (37/52). To monitor progress, therapists slightly prefer power (30/52) over velocity outputs, while few would not use them at all. Although therapists would prescribe most exercises - the squat, rotational exercise, and unilateral leg curl would be the most selected. Meanwhile, therapists reported remain most unsure or would avoid prescribing the lateral squat and unilateral hip extension. The biggest perceived barriers to flywheel training are equipment cost/space, evidence, and scheduling.